A STUDY ON INJURY PATTERNS AMONG VICTIMS OF ROAD TRAFFIC ACCIDENTS IN HARYANA (Journal of Forensic Medicine & Toxicology, 2025)
Introduction: Road accidents are one of the major contributors of death globally. Amongst the various types of accidents, road traffic accidents (RTA) are known to claim the highest number of lives. In several countries, especially in the developing countries, road traffic accidents are ranked as the top cause of death. Objective: To evaluate the pattern and distribution of injuries among individuals involved in RTA in the districts of Kurukshetra and Karnal, Haryana, India Methodology: This study was carried out in the districts of Kurukshetra and Karnal between July 2022 and July 2023. The study included 100 RTA victims. Results: A significant number (41.35%) of accidents occurred among the individuals aged 25-35 years. This was followed by the 18-25 year olds (17.29%). Heavy Vehicles were involved in 54.87% of the cases and a major part of the accidents (47%) occurred on the National Highways. Pedestrians, being the most vulnerable, accounted for 9.23 % of the total RTA followed by 28.71% of the powered two wheelers. In majority of the cases, the victims sustained grievous injuries. The highest number of injuries was recorded in the head (27.81%), and in the lower limbs (18.04%), which was followed by the chest in 7.51% cases. Vehicle occupants mostly sustained thoracic injuries. Conclusion: The complete dataset was analyzed to determine the pattern of injuries and its distribution. Male victims constituted a significant portion of the total
Keywords: wheelers; Road accidents